Fungi and mycotoxins from pre and post storage brewer’s grain intended for bovine intensive-rearing - Keller, Luiz Antonio Moura (2012)
The aim of the study was to determine the mycobiota and natural levels of mycotoxins such as aflatoxin B1 (AFB1), ochratoxin A (OTA), fumonisin B1 (FB1) and deoxinivalenol (DON) present in brewers grains pre and post stored intended for bovine intensive-rearing. Post stored (80%) samples had counts higher than 1 x 104 colony-forming units (CFU/g). Cladosporium spp., and Aspergillus spp. were isolated at high frequencies. Aspergillus flavus was the prevalent isolated species. Pre stored (70%) and post stored (100%) samples showed AFB1 levels over the recommended limits (20 µg/Kg) and OTA levels were below the recommended limits (50 µg/Kg). While pre and post stored samples did not show FB1 and DON natural contamination levels. The presence of mycotoxins in this substrate indicates the existence of contamination. Regular monitoring of feeds is required in order to prevent chronic and acute toxic syndromes related to this kind of contamination.